A Belated Green Revolution for Cannabis: Virtual Genetic Resources to Fast-Track Cultivar Development - Welling, Matthew T.; Shapter, Tim; Rose, Terry J.; Liu, Lei; Stanger, Rhia; King, Graham J. (Frontiers in Plant Science, 2016)
Cannabis is a predominantly diecious phenotypically diverse domesticated genus with few if any extant natural populations. International narcotics conventions and associated legislation have constrained the establishment, characterization and use of Cannabis genetic resource collections. This has resulted in the underutilization of genepool variability in cultivar development and has limited the inclusion of secondary genepools associated with genetic improvement strategies of the Green Revolution. The structured screening of ex situ germplasm and the exploitation of locally-adapted intraspecific traits is expected to facilitate the genetic improvement of Cannabis. However, limited attempts have been made to establish the full extent of genetic resources available for pre-breeding. We present a thorough critical review of Cannabis ex situ genetic resources, and discuss recommendations for conservation, pre-breeding characterization and genetic analysis that will underpin future cultivar development. We consider East Asian germplasm to be a priority for conservation based on the prolonged historical cultivation of Cannabis in this region over a range of latitudes, along with the apparent high levels of genetic diversity and relatively low representation in published genetic resource collections. Seed cryopreservation could improve conservation by reducing hybridization and genetic drift that may occur during Cannabis germplasm regeneration. Given the unique legal status of Cannabis, we propose the establishment of a global virtual core collection based on the collation of consistent and comprehensive provenance meta-data and the adoption of high-throughput DNA sequencing technologies. This would enable representative core collections to be used for systematic phenotyping, and so underpin breeding strategies for the genetic improvement of Cannabis.